Analisis Akuntabilitas dalam Distribusi Bantuan Sosial untuk Program Keluarga Harapan (PKH) - Pika Pristiana; Tina Kartini (Expensive: Jurnal Akuntansi dan Keuangan, 2026)
This study aims to analyze administrative accountability in the implementation of the Family Hope Program in Sirnamekar Village, particularly in updating beneficiary data. The study used a descriptive qualitative approach with purposive sampling and snowball sampling techniques. Data were collected through interviews, observation, documentation, and triangulation, with an emphasis on interpreting the findings. The results indicate that program implementation has followed official guidelines and is supported by external parties. However, the data updating process remains slow and limited regional authority in changing data in the Integrated Social Welfare Data has resulted in inaccurate targeting, resulting in some recipients who no longer meet the criteria but continue to receive assistance. Strengthening coordination and improving data updating mechanisms are needed to optimize program accountability.